Strategi Pelatihan Program Muhadharah dalam Melatih Public Speaking Siswa di SMP Muhammadiyah Sukaramai - Zaidan Zuhdi Batubara; Mavianti Mavianti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Language is an effective communication tool to convey ideas and goals. The functions of language include expressive, informational, exploratory, persuasive, and entertaining. Muhadarah is a public speaking exercise that helps students improve their public speaking skills and confidence in conveying Islamic teachings. The benefits of muhadarah include improved Arabic language ability, self-confidence, speaking skills, and book comprehension. This study used a qualitative approach with descriptive methods to describe, explain, and validate phenomena. Data collection techniques included observation, interviews, and documentation. Data validity was checked through Source Triangulation and Technique Triangulation, with data analysis through reduction, presentation, and conclusion drawing. At SMP Muhammadiyah Sukaramai, muhadarah is held regularly every Monday to Friday after Asr prayer. This activity involves all students from grades 7 to 9, with students advancing in turn. The activity begins with an opening by the teacher, followed by the delivery of material by students, and ends with an assessment by the teacher. The language used is Indonesian, and students are free to choose a theme. The purpose of this activity is to train public speaking and increase students' self-confidence. Implementation involves making a schedule, assessment, and using mats as a base. In the implementation of the memorization method, in the form of texts that have been memorized, so that the repetition of memorization is not a problem.